2019
DOI: 10.1111/gcb.14657
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal variation in soil nematode communities under climate warming‐related range‐expanding and native plants

Abstract: Current climate change has led to latitudinal and altitudinal range expansions of numerous species. During such range expansions, plant species are expected to experience changes in interactions with other organisms, especially with belowground biota that have a limited dispersal capacity. Nematodes form a key component of the belowground food web as they include bacterivores, fungivores, omnivores and root herbivores. However, their community composition under climate change‐driven intracontinental range‐expa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 64 publications
(104 reference statements)
1
49
0
Order By: Relevance
“…One of the possible mechanisms for plant invasion is enemy release: invasive plants may be more productive in their new geographic range because they have escaped consumption by natural enemies (Keane & Crawley, 2002). Compared to the long evolutionary history of the native plant with the biota, there are known examples of rapid host shifts in response to introduced plants, including one example of an herbivore feeding on S. alterniflora in China (Zhang, Ju, Pan, Pan, & Wu, 2019); however, most evidence suggests that it takes a century or more for root‐associated nematodes (Lu et al, 2018; Wilschut et al, 2019) or an entire community to adapt to a novel host species (Bezemer et al, 2013; Brändle et al, 2008; Gruntman et al, 2017). In this study, we found the opposite result: in the native range of S. alterniflora , almost no nematodes were plant‐feeders, whereas up to 17 per cent were plant‐feeders in the introduced range in China in (Appendix : Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the possible mechanisms for plant invasion is enemy release: invasive plants may be more productive in their new geographic range because they have escaped consumption by natural enemies (Keane & Crawley, 2002). Compared to the long evolutionary history of the native plant with the biota, there are known examples of rapid host shifts in response to introduced plants, including one example of an herbivore feeding on S. alterniflora in China (Zhang, Ju, Pan, Pan, & Wu, 2019); however, most evidence suggests that it takes a century or more for root‐associated nematodes (Lu et al, 2018; Wilschut et al, 2019) or an entire community to adapt to a novel host species (Bezemer et al, 2013; Brändle et al, 2008; Gruntman et al, 2017). In this study, we found the opposite result: in the native range of S. alterniflora , almost no nematodes were plant‐feeders, whereas up to 17 per cent were plant‐feeders in the introduced range in China in (Appendix : Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the well‐known geographic patterns in the diversity and abundance of aboveground organisms (Hillebrand, 2004; Mannion, Upchurch, Benson, & Goswami, 2014), the geographic patterns of belowground organisms are relatively understudied (but see Decaëns, 2010; Hendershot, Read, Henning, Sanders, & Classen, 2017; Maraun, Schatz, & Scheu, 2007). Because of the important interactions between aboveground and belowground processes, a better understanding of geographic patterns of belowground organisms is needed (Fierer, Strickland, Liptzin, Bradford, & Cleveland, 2009; Lu, He, Ding, & Siemann, 2018; van der Putten, 2012; Wilschut et al, 2019), especially in light of multiple global change factors (Bardgett & Wardle, 2010; Coyle et al, 2017) that may perturb both aboveground and belowground communities.…”
Section: Introductionmentioning
confidence: 99%
“…Together with these plant-associated organisms, other soil organisms, such as decomposers can also contribute to the net effects (the sum of positive and negative interactions) of plant-soil feedbacks during range expansions van der Putten, Bradford, Brinkman, van de Voorde, & Veen, 2016). Recent studies have shown that the community composition of soil organisms can change along the range expansion gradient (Ramirez et al, 2019;Wilschut et al, 2019). However, we have little information about how changes in the community composition of soil organisms associated to range expanding plants relate to possible differences in plant-soil feedback of these plants in their original and new range.…”
Section: Introductionmentioning
confidence: 99%
“…The online version of this article (https ://doi.org/10.1007/s0044 2-020-04749 -y) contains supplementary material, which is available to authorized users. compared to the original range (Ramirez et al 2019;Wilschut et al 2019a). Whether these soil communities from the original and new range are functionally different in terms of their impact on plant performance still remains poorly understood (Ramirez et al 2019;Van Nuland et al 2017;Wilschut et al 2019a).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%